215 Dairy calf and heifer management: nutrition, socialization and housing effects on welfare and public perception. (7th December 2018) - Costa, J
Abstract: The public is the most important stakeholder in the dairy industry; their perception of and attitudes towards other farm animal management practices has contributed to major reform of nutritional and housing requirements in the livestock industry. Thus, it is critical for the sustainability of dairy industry to ensure current practices align with the public values on animal welfare. The care of newborns generates high empathy and concern from the public. One prominent welfare concern is rearing calves in social isolation, which is associated with impairing cognitive and social development across many mammal species. The dairy calf is no exception; individually-raised calves are deficient in social and learning skills, and cope with novel situations poorly. Pairing or grouping calves prevents these deficiencies by promoting appropriate social, cognitive and behavioral development. Shifting calf management practices according to biological and scientific knowledge can also achieve the minimum expectations that the public has for calf rearing. Another major welfare concern is restricting milk intake to 4 to 6 L of milk/d; this practice is thought to encourage grain consumption, earlier weaning ages, and proper rumen development However, with limited milk intake, calves experience significant hunger and reduced weight gain, which are serious welfare concerns. Recently, there is an increased interest in feeding higher planes of nutrition with gradual weaning; these practices have resulted in positive developmental outcomes that also address welfare concerns held by the public. In conclusion, social isolation and dietary restriction are significant welfare issues and points of concern for the public for many livestock industries. These potential concerns may affect the future sustainability of the dairy industry. We suggest that group housing and enhanced milk feeding plans are examples of solutions that need industry-wide adoption to maintain a productive and welfare-focused industry that is accepted by the public in the future.